Legal Formal Cadar Sebagai Ide - Khoiruddin Manahan Siregar (IAIN Padangsidimpuan, 2022)
This study discusses the political participation of veiled students of the Padangsidimpuan State Islamic Institute in the 2019 Presidential Election in Padangsidimpuan City. This research is motivated by the fact that many female students at the Padangsidimpuan State Islamic Institute who wear the veil did not participate in the main election in the presidential election in 2019. The formulation of the problem in this study is how the political participation of students at the Islamic State Institute of Religion who are veiled women in the presidential election in 2019 in Padangsidimpuan City, how are the perceptions and what are the consequences of the perceptions of Padangsidimpuan State Islamic Institute students who are veiled in the presidential election for the state in Padangsidimpuan City, and how the rights of a Muslim woman in exercising their political rights are reviewed from the fiqh siyasah. The type of research is field research (field research), namely research conducted in the field aimed at obtaining information and describing events, events that have occurred in the field in accordance with the facts found. Data sources consist of primary and secondary, namely primary data is data obtained by researchers directly from the first hand by means of interviews and direct observations in the field. This secondary data consists of literature which is reading material, the work of experts from their respective fields which serves to explain primary legal materials. The results of the study stated that the veiled political participation of Padangsidimpuan State Islamic Institute students in the 2019 Presidential Election in Padangsidimpuan City was still very minimal, it could be seen from the level of participation of Padangsidimpuan Islamic Institute students who were veiled in the presidential election in Padangsidimpuan city which had an impact on the level of democracy that was high. exist in this country.Key word: Partisipation, Cadar, presidential election